Ab initio studies of the Rg-NO+(X1?+) van der Waals complexes (Rg = He, Ne, Ar, Kr, and Xe) - Orek, Cahit; Klos, Jacek; Lique, Francois; Bulut, Niyazi (Aip Publishing, 2016)
We used the explicitly correlated variant of the coupled clusters method with single, double, and noniterative triple excitations [CCSD(T)-F12] to compute two-dimensional potential energy surfaces of van der Waals complexes formed by rare gas atoms (Rg) and NO+(X-1 Sigma(+)) cations. We used the correlation-consistent, triple-zeta (cc-pVTZ-F12) atomic basis sets, and for Kr and Xe rare gases, we employed corresponding pseudopotential cc-pVTZ-PP-F12 atomic basis sets. These basis sets were additionally augmented with mid-bond functions. The complexes are all of skewed T-shape type with Rg atom being closer to the N-side. Using analytical representation of the potentials, we have estimated zero-point energy corrected dissociation energies from anharmonic calculations with BOUND program and also from the harmonic approximation. The binding energies increase with the polarization of the Rg atom in series from He to Xe and are 196 cm(-1), 360 cm(-1), 1024 cm(-1), 1434 cm(-1), and 2141 cm(-1), respectively. Their corresponding dissociation energies are 132 cm(-1), 300 cm(-1), 927 cm(-1), 1320 cm(-1), and 1994 cm(-1) for the complexes with He to Xe, respectively. We find good agreement with previous theoretical and experimental results. The harmonic vibrational frequencies were calculated for the bending and stretching modes of the Rg-NO+ complexes. Published by AIP Publishing.
Keywords: Center-Dot-No+; Potential-Energy Surface; Cationic Complexes; Bound-States; Photoelectron; Perturbation; Gas